Back Pain Intensity in Third Trimester Pregnant Women Participating in Prenatal Yoga - Fridawati, Rieke; Widhi Astuti, KH Endah; Satiyem, Satiyem (Poltekkes Kemenkes Surakarta, 2024)
Background: Back pain is one of the most common complaints experienced by pregnant women in the third trimester due to changes in posture, weight gain, and the effects of estrogen and progesterone hormones, which cause ligament and joint relaxation. This condition can reduce the comfort and quality of life of pregnant women. Prenatal yoga is a gentle relaxation and stretching exercise designed to increase flexibility, improve posture, and reduce muscle tension. This study aims to determine the response to back pain in pregnant women in their third trimester who participate in prenatal yoga in the Wedi Community Health Center working area. Methods: This study used a descriptive approach with total sampling technique. The study population consisted of all pregnant women in their third trimester who experienced lower back pain in the working area of the Wedi Community Health Center in Klaten Regency in 2022, totaling 42 people, all of whom were included in the sample. The research instrument used a Numeric Rating Scale (NRS) checklist to measure pain levels. Data were analyzed descriptively using frequency distribution and percentages. Results: Before participating in prenatal yoga, most pregnant women experienced moderate pain on a scale of 5, with 19 respondents (45.2%), while after participating in prenatal yoga, the pain decreased to a scale of 2 in 16 respondents (38.1%). Conclusion: Prenatal yoga has been proven to help reduce the intensity of back pain in pregnant women in their third trimester safely and effectively. It is recommended that health workers develop prenatal yoga classes in health care facilities as a promotional and preventive measure to improve the comfort and well-being of pregnant women.